Ефективне інформаційне забезпечення установи - Ханас, Ольга; Ярка, Уляна (Видавництво Львівської політехніки, 2017)
In theses presented the role and importance of information support institutions, including libraries. Essence electronic catalog as the main information ressersu libraries.
Keywords: електронний каталог; електронна бібліотека; інформаційне забезпечення; управління персоналом; інформаційне забезпечення установи